Butanol as a major product during ethanol and acetate chain elongation - Robles, Aide; Sundar, Skanda Vishnu; Mohana Rangan, Srivatsan; Delgado, Anca G. (Frontiers in Bioengineering and Biotechnology, 2023)
Chain elongation is a relevant bioprocess in support of a circular economy as it can use a variety of organic feedstocks for production of valuable short and medium chain carboxylates, such as butyrate (C4), caproate (C6), and caprylate (C8). Alcohols, including the biofuel, butanol (C4), can also be generated in chain elongation but the bioreactor conditions that favor butanol production are mainly unknown. In this study we investigated production of butanol (and its precursor butyrate) during ethanol and acetate chain elongation. We used semi-batch bioreactors (0.16 L serum bottles) fed with a range of ethanol concentrations (100–800 mM C), a constant concentration of acetate (50 mM C), and an initial total gas pressure of ~112 kPa. We showed that the butanol concentration was positively correlated with the ethanol concentration provided (up to 400 mM C ethanol) and to chain elongation activity, which produced H2 and further increased the total gas pressure. In bioreactors fed with 400 mM C ethanol and 50 mM C acetate, a concentration of 114.96 ± 9.26 mM C butanol (~2.13 g L−1) was achieved after 5 semi-batch cycles at a total pressure of ~170 kPa and H2 partial pressure of ~67 kPa. Bioreactors with 400 mM C ethanol and 50 mM C acetate also yielded a butanol to butyrate molar ratio of 1:1. At the beginning of cycle 8, the total gas pressure was intentionally decreased to ~112 kPa to test the dependency of butanol production on total pressure and H2 partial pressure. The reduction in total pressure decreased the molar ratio of butanol to butyrate to 1:2 and jolted H2 production out of an apparent stall. C. kluyveri (previously shown to produce butanol) and Alistipes (previously linked with butyrate production) were abundant amplicon sequence variants in the bioreactors during the experimental phases, suggesting the microbiome was resilient against changes in bioreactor conditions. The results from this study clearly demonstrate the potential of ethanol and acetate-based chain elongation to yield butanol as a major product. This study also supports the dependency of butanol production on limiting acetate and on high total gas and H2 partial pressures.